Positive Aspects of Dementia Caregiving: Caregivers' Lived Experiences - Indarwati, Retno; Aditama, Eka Putri; Dewi, Lingga Curnia; Haryanto, Joni; Amelia, Vira; Astuti, Trihaningsih Puji (Faculty of Nursing, Universitas Hasanuddin, 2026)
Aims: This study aims to qualitatively explore the positive experiences of caregivers for people with dementia (PwD. Methods: A descriptive phenomenological design was employed with purposive sampling. This study was conducted in Indonesia by the Alzheimer’s Indonesia organization. Participants were selected using purposive sampling methods. The study involved 11 caregivers, including paid caregivers and family members, including children, grandchildren, spouses, siblings, and other close relatives, who had provided care for at least one year. Data were collected through in-depth interviews conducted face-to-face or via Zoom in 2022. Colaizzi’s method guided the data analysis to extract significant statements, formulate their meanings, and identify emerging themes. Rigor was ensured through data triangulation, peer checking, and participant validation. Results: The study identified four main themes reflecting the positive experiences of caregivers of persons with dementia: (1) Personal Growth and Development, including increased patience, empathy, and caregiving competence; (2) improved relationships and connections, characterized by stronger emotional bonds and supportive family dynamics; (3) Search for Meaning and Role Satisfaction, where caregiving was seen as a purposeful, spiritually meaningful role; and (4) Positive Psychological Outcomes, such as reduced stress, greater emotional resilience, and enhanced well-being. Conclusion: Despite the challenges, caregiving for individuals with dementia can lead to personal growth, stronger relationships, a sense of meaning, and emotional resilience. These positive experiences highlight the importance of supporting caregivers and recognizing their strengths.